On the shoulders of giants: on the issue of the allocation of scientific schools at the faculty of philology of the Belarusian State University - Vazhnik, Syarhei A. (Journal of the Belarusian State University. Philology, 2024)
The names of philologists who have made a significant contribution to the development of the faculty of philology of the Belarusian State University are named. Currently, we cannot determine the scientific «kinship» of individual philologists, their belonging to one or another scientific school. In particular, we are talking about the definition of scientific supervisors for the PhD theses of many faculty teachers who worked at the university in the 1920–60s. It has been shown that white spots are caused by objective reasons. For the first time, scientific generations of teachers have been distinguished. The research was conducted within the framework of philological source studies. Existing sources of information have been identified and the conclusion that they are insufficient to identify all scientific schools of the faculty is made. It was found that such a genre as memoiristics is poorly developed.